Beta titanium alloy based on d-electronic alloy design theory and preparation method thereof

Through the β-titanium alloy design and thermomechanical treatment technology based on d-electronic alloy design theory, the existing β-titanium alloy has been solved, and a new low-cost and high-performance β-titanium alloy is realized.

CN119843104AActive Publication Date: 2025-04-18XIAN TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510056795.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing beta-type titanium alloys have high cost and poor performance in alloy design and performance optimization, and the microstructure and performance relationship of the multi-alloy system is complex and difficult to determine.

Method used

The method based on d-electronic alloy design theory is used to regulate the β phase stability, and the electronic characteristics of the alloy are adjusted by selecting lower-cost Fe and Nb elements, and combined with thermomechanical treatment technology, the structural structure and mechanical properties of the alloy are optimized.

Benefits of technology

It has achieved a β-titanium alloy that takes into account both low cost and high mechanical properties. It has significantly improved strength, simple preparation process and low cost, and is suitable for promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843104A_ABST
    Figure CN119843104A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials and preparation thereof, in particular to a beta titanium alloy based on the d-electronic alloy design theory and a preparation method thereof.According to the d-electronic alloy design theory, the beta titanium alloy is designed to be Ti2Al5Mo5CrxFeyNb in component composition, proportioning is conducted according to the mass percent of Ti2Al5Mo5CrxFeyNb, then vacuum melting is conducted, a cast ingot is obtained, x ranges from 1 to 3, and y ranges from 1 to 3; the cast ingot is subjected to homogenization treatment and then subjected to water cooling, and a sample before rolling is obtained; carrying out hot rolling on the sample before rolling to obtain a hot-rolled sample; carrying out solution treatment on the hot-rolled sample, and carrying out water cooling to room temperature to obtain a sample subjected to solution treatment; the sample obtained after solution treatment is subjected to aging treatment, and the beta titanium alloy obtained after aging treatment is obtained.The preparation technology is low in cost, simple in process and convenient to operate, and the prepared alloy is excellent in mechanical property and suitable for application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials and preparation thereof, and in particular to a beta titanium alloy based on d-electron alloy design theory and a preparation method thereof. Background Art

[0002] β-titanium alloy is an important category of titanium alloy. It has rich microstructural characteristics. Its unique combination of high specific strength and ductility gives it excellent comprehensive performance. The various deformation modes and phase transformation types of β-titanium alloy will also have a significant impact on its comprehensive performance. Metastable β-titanium alloy can induce phase transformation / twinning during deformation, thereby improving strength, which has potential appeal and is one of the current research hotspots.

[0003] In recent years, researchers have tried to control the β phase stability of alloys through alloy design methods, hoping to use twinning induced plasticity (TWIP) / transformation induced plasticity (TRIP) effects to introduce deformation strengthening and strength enhancement during material deformation, thereby significantly improving the strength of the material. For multi-component β titanium alloy systems, the relationship between the performance, microstructure and composition of the alloy is difficult to determine, making development even more difficult, as it involves the interaction of multiple complex alloy components and exhibits a multiphase microstructure.

[0004] At present, there are three main alloy design methods commonly used for β-type titanium alloys: Mo equivalent method, d-electron theoretical alloy design method and electron concentration method. However, it should be noted that the equivalent coefficients of each element in the MoE formula are converted based on the experimental results of binary alloys, and this method itself has a certain degree of error. Although the electron concentration method can be widely used to guide the composition design of β-type titanium alloys, it mainly considers the influence of electronic factors on the alloy phase structure. For multi-element alloy systems, in addition to electron concentration, atomic size factors are also critical. When the atomic size of alloying elements differs greatly from that of titanium atoms, lattice distortion will occur. Therefore, there are certain limitations when using only a simple electron concentration parameter to characterize the precipitation phase and properties of the alloy, and it generally needs to be used in combination with other factors. Moreover, the β-titanium alloys obtained by the existing d-electron theoretical alloy design cannot simultaneously meet the characteristics of low cost and good performance. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a β-titanium alloy based on d-electron alloy design theory and a preparation method thereof. The present invention regulates the β-phase stability of the alloy through the d-electron theory alloy design method, and expects to introduce deformation strengthening by utilizing twinning induced plasticity (TWIP) / transformation induced plasticity (TRIP) effect during material deformation to improve its strength. At the same time, reasonable heat treatment and deformation processing means can also improve the organizational structure and performance of the material, and obtain a new β-titanium alloy with good comprehensive performance. With the continuous addition of β-phase stabilizing elements Fe and Nb, the strength of the sample of the alloy is continuously improved, and the strength is significantly improved after aging treatment. In addition, the preparation technology has low cost, simple process, convenient operation, and the prepared alloy has excellent mechanical properties, which is suitable for promotion and application.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing a beta titanium alloy based on d-electron alloy design theory comprises the following steps:

[0008] The composition of the β titanium alloy is designed to be Ti2Al5Mo5CrxFeyNb through the d-electron alloy design theory, wherein x and y represent the mass percentages of Fe and Nb respectively, x is 1-3, and y is 1-3.

[0009] The materials are prepared according to the mass percentage of Ti2Al5Mo5CrxFeyNb, and then vacuum smelting is performed to obtain an ingot, wherein x is 1 to 3 and y is 1 to 3.

[0010] The ingot is homogenized and then water-cooled to obtain a sample before rolling.

[0011] The sample before rolling is hot rolled to obtain a hot rolled sample.

[0012] The hot-rolled sample is subjected to a solution treatment and then water-cooled to room temperature to obtain a solution-treated sample.

[0013] The sample after the solution treatment is subjected to aging treatment to obtain the β titanium alloy after aging treatment.

[0014] The present invention regulates the β phase stability of the alloy through the d-electron theory alloy design method, and expects to use the twinning induced plasticity / phase transformation induced plasticity effect to introduce deformation strengthening to improve its strength during the material deformation process. In terms of alloy element selection, the present invention selects alloy elements with lower costs to adjust their electronic properties (Bo and Md), thereby regulating the stability of the titanium alloy, so that it can produce phase transformation or twinning when deformed, thereby improving the plasticity and tensile strength of the titanium alloy, and obtaining a new β titanium alloy with good comprehensive performance; from a process perspective, the thermomechanical treatment technology can promote the refinement and uniform distribution of β phase grains, optimize the preparation process of β titanium alloy, thereby improving the organizational structure of β titanium alloy and improving the mechanical properties of β titanium alloy. This helps to reduce the production cost of β titanium alloy and improve the preparation efficiency and product quality of β titanium alloy.

[0015] In a preferred embodiment of the present invention, the homogenization treatment temperature is 900° C. to 1200° C., and the homogenization treatment time is 1 h to 3 h.

[0016] In a preferred embodiment of the present invention, the hot rolling method is: the sample before hot rolling is kept at 900℃~1100℃ for 10min~30min, and then hot rolled, with each pass reducing by 0.3mm~0.6mm, and kept at 900℃~1100℃ for 2min~5min after each rolling.

[0017] In a preferred embodiment of the present invention, the solution treatment temperature is 800° C. to 900° C., and the solution treatment time is 10 min to 30 min.

[0018] In a preferred embodiment of the present invention, the aging treatment temperature is 450° C. to 600° C., and the aging treatment time is 2 h to 8 h.

[0019] In a preferred embodiment of the present invention, the smelting method is to place the raw materials in order from low to high melting points into a water-cooled copper crucible vacuum non-consumable arc melting furnace for smelting.

[0020] In a preferred embodiment of the present invention, the raw materials for smelting are in the form of blocks or particles with a purity of ≥99.95%.

[0021] Another object of the present invention is to provide a β titanium alloy prepared by any of the preparation methods described above.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention designs a β-titanium alloy composition of Ti2Al5Mo5CrxFeyNb through d-electronic alloy design theory, wherein x is 1 to 3, y is 1 to 3, and the electronic properties of the alloy are adjusted by selecting Fe and Nb with lower costs, so as to obtain a β-titanium alloy with both low cost and high mechanical properties; the ingredients are prepared according to the mass percentage of Ti2Al5Mo5CrxFeyNb, and then vacuum smelting is performed to obtain an ingot, the ingot is homogenized, and then water-cooled to obtain a sample before rolling, the sample before rolling is hot-rolled to obtain a hot-rolled sample, the hot-rolled sample is solution-treated, and then water-cooled to room temperature to obtain a sample after solution treatment, and the sample after solution treatment is aged to obtain an aged β-titanium alloy. In terms of alloy element selection, the present invention selects alloy elements with lower cost to adjust its electronic properties (Bo and Md), thereby regulating the stability of the titanium alloy, enabling phase change or twinning when deformed, thereby improving the plasticity and tensile strength of the titanium alloy, and obtaining a new type of β-titanium alloy with good comprehensive performance; from a process perspective, the thermomechanical treatment technology can promote the refinement and uniform distribution of β-phase grains, optimize the preparation process of β-titanium alloy, thereby improving the organizational structure of β-titanium alloy and improving the mechanical properties of β-titanium alloy. This helps to reduce the production cost of β-titanium alloy and improve the preparation efficiency and product quality of β-titanium alloy.

[0024] 2. The present invention regulates the β phase stability of the alloy by the d-electron theory alloy design method, and expects to introduce deformation strengthening by using twin-induced plasticity / phase transformation-induced plasticity effect during the deformation process of the material to improve its strength. At the same time, reasonable heat treatment and deformation processing means can also be used to improve the organizational structure and performance of the material, and obtain a new β titanium alloy with good comprehensive performance. To obtain a high-performance titanium alloy, it is necessary to ensure the uniformity of its composition during smelting. The titanium alloy smelted in a vacuum arc melting furnace can obtain an excellent ingot with uniform composition and less impurities. After homogenization treatment, the diffusion of elements can be accelerated, the component segregation in the casting process can be eliminated, and a better foundation for subsequent processing and treatment is provided. Hot rolling can crush the coarse grains in the casting state, significantly heal cracks, reduce or eliminate casting defects, thereby optimizing the organization and improving the processing performance of the alloy. After rolling, solution treatment is carried out at high temperature, which is conducive to uniform organization and composition, and a uniform single-phase organization is obtained after rapid cooling. Aging treatment can precipitate or decompose the β titanium alloy into a second phase, which provides effective strengthening, thereby improving the strength of the titanium alloy. With the continuous addition of Fe and Nb elements, the strength of the sample continues to increase, and the strength is significantly improved after aging treatment. In addition, the preparation technology has low cost, simple process, convenient operation, and the prepared alloy has excellent mechanical properties, which is suitable for promotion and application.

[0025] 3. The present invention adopts the d-electron theoretical alloy design method to design a TiAlMoCr-based metastable β titanium alloy with TWIP / TRIP effect, and on this basis, the low-cost β-stabilizing elements Fe and Nb are used to regulate the stability of the alloy β phase, thereby regulating the plasticity and strength of the titanium alloy, and obtaining a new β titanium alloy with good comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The metallographic microstructures of the Ti2Al5Mo5CrxFeyNb alloys prepared in Examples 1 to 2 and Comparative Examples 1 to 2 of the present invention are shown in FIG. 1 , (a) Ti2Al5Mo5Cr, (b)

[0027] Ti2Al5Mo5Cr1Nb, (c) Ti2Al5Mo5Cr1Fe1Nb, (d) Ti2Al5Mo5Cr1Fe3Nb.

[0028] Figure 2 Microstructures of Ti2Al5Mo5CrxFeyNb alloys prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3, (a) Ti2Al5Mo5Cr, (b) Ti2Al5Mo5Cr1Nb, (c) Ti2Al5Mo5Cr2Nb, (d) Ti2Al5Mo5Cr1Fe1Nb, (e) Ti2Al5Mo5Cr1Fe3Nb.

[0029] Figure 3 This is a microhardness diagram of the Ti2Al5Mo5CrxFeyNb alloy in solid solution state prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3, in which the contents of Fe and Nb increase from left to right.

[0030] Figure 4 This is a microhardness diagram of the aged Ti2Al5Mo5CrxFeyNb alloy prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3, in which the contents of Fe and Nb increase from left to right.

[0031] Figure 5 Graph showing room temperature tensile engineering stress-strain curves of Ti2Al5Mo5CrxFeyNb alloys prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 2.

[0032] Figure 6 Surface metallographic structures of (a) Ti2Al5Mo5Cr and (b) Ti2Al5Mo5Cr1Fe3Nb alloy tensile specimens prepared in Comparative Example 1 and Example 2 of the present invention after fracture.

[0033] Figure 7This is a transmission microstructure diagram of the Ti2Al5Mo5Cr alloy prepared in Comparative Example 1 of the present invention after tensile deformation. DETAILED DESCRIPTION

[0034] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0036] The d-electron alloy design theory is not only one of the commonly used design methods for β-type titanium alloys, but also the current research focus. It facilitates people to understand the structural stability and strengthening mechanism of the alloy. Among them, the d-electron transition elements with unpaired spin are the main strengthening elements of β-type titanium alloys. As the covalent bond strength between their electrons gradually increases, the binding energy of the transition elements in the metal or alloy gradually increases. This theory calculates new parameters Bo and Md from the electronic structure of the alloy. The Bo and Md values ​​of the alloy are a simple linear relationship with the transformation of the components. Therefore, under the condition of knowing the alloy composition, the present invention only needs to calculate the Bo and Md values ​​of the alloy to know which type of alloy the alloy belongs to, so as to guide the amount of alloy element addition and the selection of alloy elements, reduce the experimental cost and obtain more ideal experimental results. By selecting Fe and Nb with lower cost to adjust the electronic properties of the alloy, a β-titanium alloy with both low cost and high mechanical properties is obtained, which not only provides new ideas for the development of new high-performance advanced metal materials, but also provides key alloy component selection in some fields where the performance of traditional materials has reached the limit.

[0037] The present invention adjusts the electronic properties (Bo and Md) of the alloy elements with lower cost, thereby regulating the stability of the titanium alloy so that it can produce phase change or twinning when deformed. The electronic structure of the alloy is used to calculate the new parameters Bo and Md, where Bo is used to measure the strength of the covalent bond between atoms and characterize the overlap of the electron clouds between atoms. The larger the Bo value, the higher the bonding strength between atoms; Md is used to characterize the combined influence of atomic size, electronegativity and alloying factors. According to the d-electron alloy design theory, it can be calculated by the following formula:

[0038] Formula 1 and Formula 2 are used for calculation:

[0039]

[0040] Where: i is the alloy element, X i is the atomic percentage of alloying element i.

[0041] It can be seen from formula 1 and formula 2 that the Bo and Md values ​​of the alloy are linearly related with the transformation of the components. Therefore, under the condition of knowing the alloy composition, the Bo and Md values ​​of the alloy can be calculated to infer which type of alloy the alloy belongs to, so as to help the present invention select suitable alloy elements and determine the amount of addition, so as to obtain more ideal experimental results on the basis of reducing costs. According to the alloy design target of the present invention, the Bo and Md of the designed composition are selected to be in the region of 2.783-2.787 and 2.348-2.368, respectively, and based on cost considerations, Fe and Nb with lower costs are finally selected to adjust their electronic properties (Bo and Md), and their organizational properties are studied.

[0042] Example 1

[0043] A method for preparing a Ti2Al5Mo5Cr1Fe1Nbβ titanium alloy comprises the following steps:

[0044] (1) The ingredients are weighed by an electronic balance according to the mass percentage of Ti2Al5Mo5Cr1Fe1Nb. The raw materials used are all in the form of blocks or particles with a purity of ≥99.95%. The raw materials are placed in a water-cooled copper crucible vacuum non-consumable arc melting furnace in order of melting point from low to high. The vacuum is drawn to 2×10 -3 Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% and then melt it. Before melting the raw materials, melt the sponge titanium for two to three minutes, and control the current at 630A. To ensure uniform composition, the titanium alloy ingot is turned over at least 5 times, and finally a round cake-shaped ingot is obtained.

[0045] (2) The circular ingot was cut into blocks with a length × width × height of 40 mm × 30 mm × 13.5 mm in radial direction by wire electrospark cutting. The blocks were then placed in a high-temperature resistant quartz glass tube with sponge titanium at the bottom and sealed with a hydrogen-oxygen tube sealing machine. During the process, the tube was evacuated and filled with protective gas argon to reduce the air in the glass tube and prevent oxidation. The as-cast test block was homogenized at 1100°C for 2 h and then water-cooled to obtain the sample before rolling.

[0046] (3) After grinding away the oxide layer and edges of the sample before rolling, the sample was kept at 940°C for 20 min and then hot rolled along the length of the block. The reduction in each pass was 0.5 mm, and the sample was kept at 940°C for 3 min after each rolling, and finally a strip-shaped sample with a thickness of about 2.5 mm was obtained.

[0047] (4) The rolled sample is solution treated at 870°C for 20 min and finally cooled to room temperature by water to obtain a sample of the rolled alloy after solution treatment.

[0048] (5) The sample of the rolled alloy after solid solution treatment was cut into a block with a length × width × height of 7 mm × 7 mm × 2.5 mm by using the electric spark wire cutting method, and then aged for 4 h at 550°C to obtain the aged sample.

[0049] Example 2

[0050] A method for preparing a Ti2Al5Mo5Cr1Fe3Nbβ titanium alloy comprises the following steps:

[0051] (1) The ingredients are weighed by an electronic balance according to the mass percentage of Ti2Al5Mo5Cr1Fe3Nb. The raw materials used are in the form of blocks or particles with a purity of ≥99.95%. The raw materials are placed in a water-cooled copper crucible vacuum non-consumable arc melting furnace in order of melting point from low to high. The vacuum is drawn to 2×10 -3 Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% and then melt it. Before melting the raw materials, melt the sponge titanium for two to three minutes, and control the current at 630A. To ensure uniform composition, the titanium alloy ingot is turned over at least 5 times, and finally a round cake-shaped ingot is obtained.

[0052] (2) The circular ingot was cut into blocks with a length × width × height of 40 mm × 30 mm × 13.5 mm in radial direction by wire electrospark cutting. The blocks were then placed in a high-temperature resistant quartz glass tube with sponge titanium at the bottom and sealed with a hydrogen-oxygen tube sealing machine. During the process, the tube was evacuated and filled with protective gas argon to reduce the air in the glass tube and prevent oxidation. The as-cast test block was homogenized at 1100°C for 2 h and then water-cooled to obtain the sample before rolling.

[0053] (3) After grinding away the oxide layer and edges of the sample before rolling, the sample was kept at 940°C for 20 min and then hot rolled along the length of the block. The reduction in each pass was 0.5 mm, and the sample was kept at 940°C for 3 min after each rolling, and finally a strip-shaped sample with a thickness of about 2.5 mm was obtained.

[0054] (4) The rolled sample is solution treated at 870°C for 20 min and finally cooled to room temperature by water to obtain a sample of the rolled alloy after solution treatment.

[0055] (5) The sample of the rolled alloy after solid solution treatment was cut into a block with a length × width × height of 7 mm × 7 mm × 2.5 mm by using the electric spark wire cutting method, and then aged for 4 h at 550°C to obtain the aged sample.

[0056] Example 3

[0057] A method for preparing a Ti2Al5Mo5Cr1Fe3Nbβ titanium alloy comprises the following steps:

[0058] (1) The ingredients are weighed by an electronic balance according to the mass percentage of Ti2Al5Mo5Cr1Fe3Nb. The raw materials used are in the form of blocks or particles with a purity of ≥99.95%. The raw materials are placed in a water-cooled copper crucible vacuum non-consumable arc melting furnace in order of melting point from low to high. The vacuum is drawn to 2×10 -3 Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% and then melt it. Before melting the raw materials, melt the sponge titanium for two to three minutes, and control the current at 600A. To ensure uniform composition, the titanium alloy ingot is turned over at least 5 times, and finally a round cake-shaped ingot is obtained.

[0059] (2) The circular ingot was cut into blocks with a length × width × height of 40 mm × 30 mm × 13.5 mm in radial direction by wire electrospark cutting. The blocks were then placed in a high-temperature resistant quartz glass tube with sponge titanium at the bottom and sealed with a hydrogen-oxygen tube sealing machine. During the process, the tube was evacuated and filled with protective gas argon to reduce the air in the glass tube and prevent oxidation. The as-cast test block was homogenized at 900 °C for 1 h and then water-cooled to obtain the sample before rolling.

[0060] (3) After grinding away the oxide layer and edges of the sample before rolling, the sample was kept at 900°C for 10 min and then hot rolled along the length of the block. The reduction in each pass was 0.3 mm, and the sample was kept at 900°C for 2 min after each rolling, and finally a strip-shaped sample with a thickness of about 2.5 mm was obtained.

[0061] (4) The rolled sample is solution treated at 800°C for 30 min and finally cooled to room temperature by water to obtain a sample of the rolled alloy after solution treatment.

[0062] (5) The sample of the rolled alloy after solution treatment was cut into a block with a length × width × height of 7 mm × 7 mm × 2.5 mm by using the electric spark wire cutting method, and then aged for 8 h at 450°C to obtain the aged sample.

[0063] Example 4

[0064] A method for preparing a Ti2Al5Mo5Cr1Fe3Nbβ titanium alloy comprises the following steps:

[0065] (1) The ingredients are weighed by an electronic balance according to the mass percentage of Ti2Al5Mo5Cr1Fe3Nb. The raw materials used are in the form of blocks or particles with a purity of ≥99.95%. The raw materials are placed in a water-cooled copper crucible vacuum non-consumable arc melting furnace in order of melting point from low to high. The vacuum is drawn to 2×10 -3 Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% and then melt it. Before melting the raw materials, melt the sponge titanium for two to three minutes, and control the current at 650A. To ensure uniform composition, the titanium alloy ingot is turned over at least 5 times, and finally a round cake-shaped ingot is obtained.

[0066] (2) The circular ingot was cut into blocks with a length × width × height of 40 mm × 30 mm × 13.5 mm in radial direction by wire electrospark cutting. The blocks were then placed in a high-temperature resistant quartz glass tube with sponge titanium at the bottom and sealed with a hydrogen-oxygen tube sealing machine. During the process, the tube was evacuated and filled with protective gas argon to reduce the air in the glass tube and prevent oxidation. The as-cast test block was homogenized at 1200°C for 3 h and then water-cooled to obtain the sample before rolling.

[0067] (3) After grinding away the oxide layer and edges of the sample before rolling, the sample was kept at 1100°C for 30 min and then hot rolled along the length of the block. The reduction in each pass was 0.6 mm, and the sample was kept at 110°C for 5 min after each rolling, and finally a strip sample with a thickness of about 2.5 mm was obtained.

[0068] (4) The rolled sample is solution treated at 900°C for 10 min and finally cooled to room temperature by water to obtain a sample of the rolled alloy after solution treatment.

[0069] (5) The sample of the rolled alloy after solid solution treatment was cut into a block with a length × width × height of 7 mm × 7 mm × 2.5 mm by using the electric spark wire cutting method, and then aged at 600 ° C for 2 h to obtain the aged sample.

[0070] Comparative Example 1

[0071] A method for preparing a Ti2Al5Mo5Crβ titanium alloy comprises the following steps:

[0072] (1) The ingredients are weighed by an electronic balance according to the mass percentage of Ti2Al5Mo5Cr. The raw materials used are in the form of blocks or particles with a purity of ≥99.95%. The raw materials are placed in a water-cooled copper crucible vacuum non-consumable arc melting furnace in order of melting point from low to high. The vacuum is drawn to 2×10 -3 Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% and then melt it. Before melting the raw materials, melt the sponge titanium for two to three minutes, and control the current at 630A. To ensure uniform composition, the titanium alloy ingot is turned over at least 5 times, and finally a round cake-shaped ingot is obtained.

[0073] (2) The circular ingot was cut into blocks with a length × width × height of 40 mm × 30 mm × 13.5 mm in radial direction by wire electrospark cutting. The blocks were then placed in a high-temperature resistant quartz glass tube with sponge titanium at the bottom and sealed with a hydrogen-oxygen tube sealing machine. During the process, the tube was evacuated and filled with protective gas argon to reduce the air in the glass tube and prevent oxidation. The as-cast test block was homogenized at 1100°C for 2 h and then water-cooled to obtain the sample before rolling.

[0074] (3) After grinding away the oxide layer and edges of the sample before rolling, the sample was kept at 940°C for 20 min and then hot rolled along the length of the block. The reduction in each pass was 0.5 mm, and the sample was kept at 940°C for 3 min after each rolling, and finally a strip-shaped sample with a thickness of about 2.5 mm was obtained.

[0075] (4) The rolled sample is solution treated at 870°C for 20 min and finally cooled to room temperature by water to obtain a sample of the rolled alloy after solution treatment.

[0076] (5) The sample of the rolled alloy after solid solution treatment was cut into a block with a length × width × height of 7 mm × 7 mm × 2.5 mm by using the electric spark wire cutting method, and then aged for 4 h at 550°C to obtain the aged sample.

[0077] Comparative Example 2

[0078] A method for preparing a Ti2Al5Mo5Cr1Nbβ titanium alloy comprises the following steps:

[0079] (1) The ingredients are weighed by an electronic balance according to the mass percentage of Ti2Al5Mo5Cr1Nb. The raw materials used are in the form of blocks or particles with a purity of ≥99.95%. The raw materials are placed in a water-cooled copper crucible vacuum non-consumable arc melting furnace in order of melting point from low to high. The vacuum is drawn to 2×10-3 Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% and then melt it. Before melting the raw materials, melt the sponge titanium for two to three minutes, and control the current at 630A. To ensure uniform composition, the titanium alloy ingot is turned over at least 5 times, and finally a round cake-shaped ingot is obtained.

[0080] (2) The circular ingot was cut into blocks with a length × width × height of 40 mm × 30 mm × 13.5 mm in radial direction by wire electrospark cutting. The blocks were then placed in a high-temperature resistant quartz glass tube with sponge titanium at the bottom and sealed with a hydrogen-oxygen tube sealing machine. During the process, the tube was evacuated and filled with protective gas argon to reduce the air in the glass tube and prevent oxidation. The as-cast test block was homogenized at 1100°C for 2 h and then water-cooled to obtain the sample before rolling.

[0081] (3) After grinding away the oxide layer and edges of the sample before rolling, the sample was kept at 940°C for 20 min and then hot rolled along the length of the block. The reduction in each pass was 0.5 mm, and the sample was kept at 940°C for 3 min after each rolling, and finally a strip-shaped sample with a thickness of about 2.5 mm was obtained.

[0082] (4) The rolled sample is solution treated at 870°C for 20 min and finally cooled to room temperature by water to obtain a sample of the rolled alloy after solution treatment.

[0083] (5) The sample of the rolled alloy after solid solution treatment was cut into a block with a length × width × height of 7 mm × 7 mm × 2.5 mm by using the electric spark wire cutting method, and then aged for 4 h at 550°C to obtain the aged sample.

[0084] Comparative Example 3

[0085] A method for preparing a Ti2Al5Mo5Cr2Nbβ titanium alloy comprises the following steps:

[0086] (1) The ingredients are weighed by an electronic balance according to the mass percentage of Ti2Al5Mo5Cr2Nb. The raw materials used are all in the form of blocks or particles with a purity of ≥99.95%. The raw materials are placed in a water-cooled copper crucible vacuum non-consumable arc melting furnace in order of melting point from low to high. The vacuum is drawn to 2×10 -3 Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% and then melt it. Before melting the raw materials, melt the sponge titanium for two to three minutes, and control the current at 630A. To ensure uniform composition, the titanium alloy ingot is turned over at least 5 times, and finally a round cake-shaped ingot is obtained.

[0087] (2) The circular ingot was cut into blocks with a length × width × height of 40 mm × 30 mm × 13.5 mm in radial direction by wire electrospark cutting. The blocks were then placed in a high-temperature resistant quartz glass tube with sponge titanium at the bottom and sealed with a hydrogen-oxygen tube sealing machine. During the process, the tube was evacuated and filled with protective gas argon to reduce the air in the glass tube and prevent oxidation. The as-cast test block was homogenized at 1100°C for 2 h and then water-cooled to obtain the sample before rolling.

[0088] (3) After grinding away the oxide layer and edges of the sample before rolling, the sample was kept at 940°C for 20 min and then hot rolled along the length of the block. The reduction in each pass was 0.5 mm, and the sample was kept at 940°C for 3 min after each rolling, and finally a strip-shaped sample with a thickness of about 2.5 mm was obtained.

[0089] (4) The rolled sample is solution treated at 870°C for 20 min and finally cooled to room temperature by water to obtain a sample of the rolled alloy after solution treatment.

[0090] (5) The sample of the rolled alloy after solid solution treatment was cut into a block with a length × width × height of 7 mm × 7 mm × 2.5 mm by using the electric spark wire cutting method, and then aged for 4 h at 550°C to obtain the aged sample.

[0091] The sample of the rolled alloy after solution treatment was cut into 16.4mm×43mm hook-type tensile specimens by electric spark wire cutting method; grinding and polishing cleaning: first grind it smooth with 80-2000# SiC sandpaper, then electropolish it, and finally clean it with anhydrous ethanol in an ultrasonic cleaner for 10 minutes, take it out and blow dry it for use.

[0092] Results Analysis

[0093] Figure 1 The metallographic microstructures of the Ti2Al5Mo5CrxFeyNb alloys prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 are shown in (a) to (d) as follows: Fe and Nb contents increase in sequence: Figure 1 It can be seen that the alloys are composed of coarse β-phase grains with uniform grain size. The results show that the alloys obtain a single β-phase grain structure after solution treatment.

[0094] Figure 2The microscopic morphology of the Ti2Al5Mo5CrxFeyNb alloy prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3, (a) to (e) the Fe and Nb contents increase successively. It can be seen that at an aging temperature of 550°C, needle-shaped α phases are precipitated at the grain boundaries and in the grains of the Ti2Al5Mo5Cr alloy. The α phase precipitated on the grain boundaries is significantly coarser than the α phase precipitated in the grains, which may be related to the ease with which solute atoms diffuse to the grain boundaries, and the α phase at the grain boundaries is continuously distributed. A large amount of needle-shaped α phases are precipitated at the grain boundaries and in the grains of the Ti2Al5Mo5Cr1Nb alloy, and part of the α phase at the grain boundaries is precipitated continuously. By comparison, it can be obtained that under the same aging time, the size of the precipitated α phase in different alloys increases with the increase of β-phase stabilizing elements, especially the precipitated α phase changes the most with the increase of Fe content. It can be clearly seen from the figure that the alloy without the addition of Fe element has little effect on the precipitation change of α phase. The α phase is needle-shaped, while the α phase size change trend is obvious in the alloy with the addition of Fe element.

[0095] Figure 3 The microhardness diagram of the Ti2Al5Mo5CrxFeyNb alloy in the solid solution state prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3. The contents of Fe and Nb increase from left to right. It can be seen that after adding 1% Nb to the Ti2Al5Mo5Cr-based alloy, the hardness of the material is slightly improved. On this basis, adding another 1% Fe can be found that the hardness of the material is significantly improved. The results show that adding β-stabilizing elements Fe and Nb to the Ti2Al5Mo5Cr matrix can significantly improve the hardness of the material, and the Fe element has a significantly stronger effect on improving the hardness of the Ti2Al5Mo5Cr alloy than the Nb element. Figure 4 This is the microhardness diagram of the aged Ti2Al5Mo5CrxFeyNb alloy prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3. The contents of Fe and Nb increase from left to right, and a second phase is generated after aging treatment, which significantly improves the hardness of the alloy.

[0096] Figure 5 The room temperature tensile engineering stress-strain curves of Ti2Al5Mo5CrxFeyNb alloys prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 are shown. It can be seen from the figure that with the addition of β-phase stabilizing elements, the strength of the alloy is significantly improved, while the plasticity is lost.

[0097] Figure 6The metallographic structures of the (a) Ti2Al5Mo5Cr and (b) Ti2Al5Mo5Cr1Fe3Nb alloy tensile specimens prepared in Comparative Example 1 and Example 2 of the present invention after fracture. The linear features of the Ti2Al5Mo5Cr sample are not as clear as those of the Ti2Al5Mo5Cr1Fe3Nb sample. It is possible that in addition to slip, phase transformation also occurred in the Ti2Al5Mo5Cr sample. The results of subsequent TEM observations are as follows: Figure 7 As shown in the figure, it can be seen that the transmission microstructure of the Ti2Al5Mo5Cr alloy after tensile deformation is mainly martensite produced by phase transformation, with a small amount of twins. Most of the slip lines of the Ti2Al5Mo5Cr1Fe3Nb sample are relatively clear, and the relatively coarse linear features that appear after tensile fracture can be judged from the morphology, which may be the deformation twins. Figure 6 (b). In some places, it can be observed that the slip traces in the grains have a good orientation relationship with the slip traces in the adjacent grains. This grain boundary is a special grain boundary. Therefore, in general, with the continuous addition of Fe and Nb elements, the plasticity of the alloy specimens continues to decrease and the strength continues to increase. The Ti2Al5Mo5Cr alloy has the best plasticity, and the Ti2Al5Mo5Cr1Fe3Nb alloy has the highest strength.

[0098] In summary, the present invention regulates the β-phase stability of the alloy through the d-electron theory alloy design method, and expects to use the twinning-induced plasticity / phase transformation-induced plasticity effect to introduce deformation strengthening to improve its strength during the deformation of the material. In terms of alloy element selection, the present invention selects alloy elements with lower costs to adjust their electronic properties (Bo and Md), thereby regulating the stability of the titanium alloy, so that it can produce phase transformation or twinning when deformed, thereby improving the plasticity and tensile strength of the titanium alloy, and obtaining a new β-titanium alloy with good comprehensive performance; from a process perspective, thermomechanical treatment technology can promote the refinement and uniform distribution of β-phase grains, optimize the preparation process of β-titanium alloys, thereby improving the organizational structure of β-titanium alloys and improving the mechanical properties of β-titanium alloys. This helps to reduce the production cost of β-titanium alloys and improve the preparation efficiency and product quality of β-titanium alloys.

[0099] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0100] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a β-titanium alloy based on d-electron alloy design theory, characterized in that: The following steps are involved: The composition of the β-titanium alloy is designed to be Ti2Al5Mo5CrxFeyNb by the d-electron alloy design theory, wherein x and y represent the mass percentages of Fe and Nb, respectively, x is 1 to 3, and y is 1 to 3; The materials are prepared according to the mass percentage of Ti2Al5Mo5CrxFeyNb, and then vacuum smelted to obtain an ingot; The ingot is homogenized and then water-cooled to obtain a sample before rolling, and the sample before rolling is hot-rolled to obtain a sample after hot rolling; The hot-rolled sample is subjected to a solution treatment, and then water-cooled to room temperature to obtain a solution-treated sample. The solution-treated sample is subjected to an aging treatment to obtain an aged β-titanium alloy.

2. The method for preparing a β-titanium alloy based on d-electron alloy design theory according to claim 1, characterized in that: The homogenization treatment temperature is 900°C to 1200°C, and the homogenization treatment time is 1h to 3h.

3. The method for preparing a β-titanium alloy based on d-electron alloy design theory according to claim 1, characterized in that: The hot rolling method is: keep the sample before hot rolling at 900℃~1100℃ for 10min~30min, then carry out hot rolling, the rolling reduction for each pass is 0.3mm~0.6mm, and keep at 900℃~1100℃ for 2min~5min after each rolling.

4. The method for preparing a β-titanium alloy based on d-electron alloy design theory according to claim 1, characterized in that: The solution treatment temperature is 800°C to 900°C, and the solution treatment time is 10min to 30min.

5. The method for preparing a β-titanium alloy based on d-electron alloy design theory according to claim 1, characterized in that: The aging treatment temperature is 450°C to 600°C, and the aging treatment time is 2h to 8h.

6. The method for preparing a β-titanium alloy based on d-electron alloy design theory according to claim 1, characterized in that: The smelting method is to place the raw materials in order from low to high melting points into a water-cooled copper crucible vacuum non-consumable arc melting furnace for smelting.

7. The method for preparing a β-titanium alloy based on d-electron alloy design theory according to claim 1, characterized in that: The raw materials for smelting are in the form of blocks or granules with a purity of ≥99.95%.

8. A β-titanium alloy based on d-electron alloy design theory obtained by the preparation method according to any one of claims 1 to 7.

9. The β-titanium alloy based on d-electron alloy design theory according to claim 8, characterized in that: The Bo value of the β titanium alloy is 2.783-2.787, and the Md value is 2.348-2.368.

Citation Information

Patent Citations

  • Beta titanium alloy and preparation method thereof

    CN101886188A

  • Ultrahigh-strength and ductility low-cost titanium alloy and preparation method and application thereof

    CN108486410A

  • Beta-type Ti-V-Fe-Nb-Al alloy with {332} twinning induced plasticity effect

    CN117965953A

  • High-strength and high-plasticity titanium alloy and preparation method thereof

    CN119040692A

  • High-specific-strength multistage twin-crystal martensite structure titanium alloy and preparation method thereof

    CN119120985A